Pengaruh Insentif dan Pelatihan terhadap Kinerja Karyawan Bank Syariah Syariah Mandiri Kantor Cabang Balikpapan - Ahmad Syarif (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2021)
Human resources are one of the most important assets of a company. Improving the quality of human resources aims to improve employee performance in a productive and professional manner. Employee contributions can have an impact on the company because if an employee performs well, they will also make a good contribution. The company's provision of salaries in the form of incentives and training is aimed at improving the performance of Branch Office of Bank Syariah Mandiri’s employees at Balikapapn. Therefore, this study aims to examine the effect of incentives and training on employee performance. This study uses quantitative methods with a number of respondents up to 45 employees of Bank Syariah Mandiri. This study uses multiple linear regression. In some cases, incentives have no effect on employee performance, while the provision of training has a significant positive effect on employee performance.